CURATOR'S RESPONSIBILITIES IN SETTLEMENT THE ASSETS OF THE BANKRUPT DEBTOR AGAINST CREDITOR'S CLAIM BY WORKERS ON STATE-OWNED ENTERPRISE PT. PERSERO - Bobby Wijanarko; Catharina Dewi Wulansari; Sentosa Sembiring (RADJA PUBLIKA, 2026)
This study aims to examine and analyze the legal responsibilities of the Curator in settlement of the assets of bankrupt debtors against the workers' creditors' claims at PT Persero . The issues raised is b how implementation not quite enough answer Curator in bankruptcy moment carry out settlement treasure debtor bankruptcy of PT Persero against bill creditors workers to achieve justice . Research This use method research socio- legal which is approach interdisciplinary combine all aspect perspective discipline science , science social and science law , to be a approach single . With combine method juridical normative in study law that focuses on analysis against existing legal norms​ in regulation legislation and theory law as well as principles law . This method focus on study to regulation applicable law ( law​ positive ) and existing norms in look for answer to problems and from study later expected can strengthen the concept that has been there is something related with not quite enough answer law Curator in do settlement treasure the wealth of PT Persero which has stated bankrupt to bill creditors workers Research result This show that not quite enough answer Curator in bankruptcy moment carry out settlement treasure debtor bankruptcy of PT Persero against bill creditors worker Not yet fully fulfil Pancasila justice . This caused by Still there is other factors that influence implementation task from curator and cause fulfillment principle justice felt creditors worker in the process of being sorted out . There is other factors that influence task Curator that can​ recommended with change draft existing responsibilities​ in provision Constitution Bankruptcy and PKPU become more wide namely related responsibility answer on error or his negligence in administration and settlement treasure bankrupt when cause loss for treasure bankrupt or creditors . But it is also related with not quite enough answer professional in implementation his duties curator subject to the code ethics profession and the principle of fiduciary duty, namely moral and legal obligations to act in interest recipient trust ( creditors and assets) bankrupt ).